Priority Development Areas: a New Tool for Attracting Investment in the Far East of Russia - Kashina, Nadezhda Viktorovna (Economy of Regions, 2016)
The purpose of the article is to compare the new term for the Russian economy - «priority development areas (PDA)» with the existing concepts of «special economic zone (SEZ)» and «regional development zones (RDZ)». In the article, the characteristics of territories with a special tax regime and its benefits for investors are examined. The subject matter of the research are the conditions that shape the favourable environment of investment activity due to the provided state support in newly created priority development areas in comparison with the existing tools, such as special economic zones and zones of territorial development. It is hypothesized that there is a direct link between the existence of tax benefits and other forms of the state support of investors provided in a territory with a special tax regime, and the attraction of investors to the region. In the study, the method of comparative analysis and statistical grouping methods are used. The common features of the analyzed types of territories are revealed according to certain characteristics; these are the federal status and the special regime of the investment activity implementation. In the article, their distinctive features such as the terms of creation, management of territories and measures of the state support are substantiated. The results of the research presented in the article confirm that the residents of newly created priority development areas in the Far East have more competitive and preferential terms for business in comparison with the residents of special economic zones and zones of territorial development in the Russian Federation. In the article, the administrative risks of the transfer of authority for the management of territories to the private companies are substantiated. The absence of interrelation between the declared specialization of the created priority development areas with the special regime of business activity and the types of economic activity determined by the resolutions of the Russian government for the certain territories where the preferential legal regime works, is revealed. This increases the insufficient tax yield in the regions as the benefits are granted to non-priority activities. The proposals for the legal response to the revealed problems have been formulated. The results of the research may be used by the federal and regional authorities in forming the proposals for updating the laws and other regulations in the sphere of the creation of the territories with the special regime for investors.